2021
DOI: 10.7150/jca.59933
|View full text |Cite
|
Sign up to set email alerts
|

Hallmark microRNA signature in liquid biopsy identifies hepatocellular carcinoma and differentiates it from liver metastasis

Abstract: This study aims to develop a liquid biopsy assay to identify HCC and differentially diagnose hepatocellular carcinoma (HCC) from colorectal carcinoma (CRC) liver metastasis. Methods: Thirty-two microRNAs ("HallMark-32" panel) were designed to target the ten cancer hallmarks in HCC. Quantitative PCR and supervised machine learning models were applied to develop an HCC-specific diagnostic model. One hundred thirty-three plasma samples from intermediate-stage HCC patients, colorectal cancer (CRC) patients with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…miR-30c-5p studied here has been shown to be involved in other cancers such as colorectal cancer [ 32 , 33 ], non-small cell lung cancer [ 34 , 35 ], gastric cancer [ 36 ], pancreatic ductal adenocarcinoma [ 37 ], renal cell carcinoma [ 38 , 39 ], hepatocellular carcinoma [ 40 , 41 , 42 , 43 ], breast cancer [ 44 , 45 , 46 , 47 , 48 ], laryngeal cancer [ 49 ], and other malignancies. For example, in gastric cancer, miR-30c-5p suppresses migration, invasion, and epithelial to mesenchymal transition via targeting MTA1 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-30c-5p studied here has been shown to be involved in other cancers such as colorectal cancer [ 32 , 33 ], non-small cell lung cancer [ 34 , 35 ], gastric cancer [ 36 ], pancreatic ductal adenocarcinoma [ 37 ], renal cell carcinoma [ 38 , 39 ], hepatocellular carcinoma [ 40 , 41 , 42 , 43 ], breast cancer [ 44 , 45 , 46 , 47 , 48 ], laryngeal cancer [ 49 ], and other malignancies. For example, in gastric cancer, miR-30c-5p suppresses migration, invasion, and epithelial to mesenchymal transition via targeting MTA1 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA-30c-5p could suppress breast cancer survival by targeting KRAS Proto-Oncogene 38 , or histone deacetylase 9 (HDAC9) gene 39 . A recent study reported that miR-30c-5p was significantly decreased in the blood of HCC patients and could effectively discriminate HCC patients from healthy individuals 40 . There were also several studies on miR-30c-5p in GC.…”
Section: Discussionmentioning
confidence: 99%
“…In the development and progression of pancreatic cancer, miR-30 c had vital functions by targeting twinfilin 1 (TWF1) [ 28 ] or DNA topoisomerase II alpha gene (TOP2A) [ 29 ]. Because the expression of miR-30 c was significantly down-regulated in the plasma of HCC samples, it might be used as a noninvasive diagnostic marker [ 30 ]. The urinary exosome miR-30 c was also suggested as a biomarker of clear cell renal cell carcinoma [ 31 ].…”
Section: Discussionmentioning
confidence: 99%